2021
DOI: 10.3390/polym13162740
|View full text |Cite
|
Sign up to set email alerts
|

SEM/EDS Evaluation of the Mineral Deposition on a Polymeric Composite Resin of a Toothpaste Containing Biomimetic Zn-Carbonate Hydroxyapatite (microRepair®) in Oral Environment: A Randomized Clinical Trial

Abstract: Toothpastes containing biomimetic hydroxyapatite have been investigated in recent years; the behavior of this material in the oral environment has been evaluated directly on dental enamel showing a marked remineralizing activity. To propose microRepair®-based toothpastes (Zn-carbonate hydroxyapatite) for the domiciliary oral hygiene in patients with dental composite restorations, the aim of this study was to evaluate the deposition of Zn-carbonate hydroxyapatite on a polymeric composite resin with Scanning Ele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
47
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 63 publications
(47 citation statements)
references
References 29 publications
(37 reference statements)
0
47
0
Order By: Relevance
“…It is also important to notice that chlorhexidine should be used for a maximum of 15 days (with a worsening of periodontal indexes at the end of the period), differently from postbiotics. In addition to the effect on soft tissues, it is also remarkable that Biorepair Parodontgel Intensive contains biomimetic Zn-Carbonate Hydroxyapatite, which is recognized for its significant effect on tooth remineralization [ 14 ]. Therefore, while chlorhexidine has acted only as an antimicrobial agent, the experimental product here considered might have caused multiple effects on both soft and hard tissues.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is also important to notice that chlorhexidine should be used for a maximum of 15 days (with a worsening of periodontal indexes at the end of the period), differently from postbiotics. In addition to the effect on soft tissues, it is also remarkable that Biorepair Parodontgel Intensive contains biomimetic Zn-Carbonate Hydroxyapatite, which is recognized for its significant effect on tooth remineralization [ 14 ]. Therefore, while chlorhexidine has acted only as an antimicrobial agent, the experimental product here considered might have caused multiple effects on both soft and hard tissues.…”
Section: Discussionmentioning
confidence: 99%
“…In spite of its efficacy, bacterial recolonization following the treatment is the most represented shortcoming of SRP [ 9 ]. On the basis of this consideration, further therapeutic approaches have been proposed as adjuncts, like the use of antibiotics [ 10 ], the photodynamic treatment [ 11 ], ozone application [ 12 ], and, in recent years, probiotic therapy [ 13 , 14 ]. As regards these last ones, they have been used more and more in recent years for the treatment of periodontal conditions because of the avoidance of the side effects related to the conventional antibiotic therapy [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…Conversely, several studies [ 25 ] have shown that biomimetic hydroxyapatite even leads to a mineral deposition, thus forming a real coating on enamel and dental surfaces [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, our results should be interpreted in a global picture as new alternatives are rising to aid the battle against marginal degradation and secondary caries. For example, recent research has shown the deposition of hydroxyapatite on polymeric resin composite [ 45 ]. This could represent additional help in the prevention of secondary caries on the margins of restorations.…”
Section: Discussionmentioning
confidence: 99%